2013
DOI: 10.1007/s10654-013-9852-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole grain and refined grain consumption and the risk of type 2 diabetes: a systematic review and dose–response meta-analysis of cohort studies

Abstract: Several studies have suggested a protective effect of intake of whole grains, but not refined grains on type 2 diabetes risk, but the dose-response relationship between different types of grains and type 2 diabetes has not been established. We conducted a systematic review and meta-analysis of prospective studies of grain intake and type 2 diabetes. We searched the PubMed database for studies of grain intake and risk of type 2 diabetes, up to June 5th, 2013. Summary relative risks were calculated using a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
311
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(334 citation statements)
references
References 65 publications
7
311
1
5
Order By: Relevance
“…However, it deserves some attention because the present case study was carried for more than 2 years and the results obtained are consistent and encouraging. This study supports the suggestions made by Aune et al (2013), 'to include at least two servings of whole grains per day in the diet to reduce type 2 diabetes risk [16]. Wheat porridge, a whole grain meal, is easy for the patients to make and hence can be included in their diet.…”
Section: Discussionsupporting
confidence: 86%
“…However, it deserves some attention because the present case study was carried for more than 2 years and the results obtained are consistent and encouraging. This study supports the suggestions made by Aune et al (2013), 'to include at least two servings of whole grains per day in the diet to reduce type 2 diabetes risk [16]. Wheat porridge, a whole grain meal, is easy for the patients to make and hence can be included in their diet.…”
Section: Discussionsupporting
confidence: 86%
“…23,40 Many of these other food sources, which tend to be sweetened with sucrose, have either shown no association (e.g., cakes and cookies, 41 and sherbert 42 ) or a protective association (e.g., whole-grain cereals, fruit, yogurt and even ice cream [42][43][44] ) with type 2 diabetes (Appendix 2, available at www.cmaj.ca/ lookup/suppl/doi:10.1503/cmaj.160706/-/DC1). An inverse doseresponse gradient, similar to that for sucrose, has even been found for whole-grain cereals, fruit and yogurt.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse doseresponse gradient, similar to that for sucrose, has even been found for whole-grain cereals, fruit and yogurt. [42][43][44] Taken together, lack of an adverse association between intakes of total sugars, fructose or sucrose and diabetes may reflect important contributions from these other food sources.…”
Section: Discussionmentioning
confidence: 99%
“…Intake of whole grains is associated with reduced risk of several non-communicable diseases, as opposed to refined grains [24,25]. A study on fish intake reported adverse effects on markers of metabolic syndrome from processed fish, whereas whole fish seems to protect [26].…”
mentioning
confidence: 99%